Mapping the research landscape of job embeddedness and turnover: A bibliometric analysis using CiteSpace - Xin, Chen; Mansor, Azlin Norhaini; Amat, Salleh Bin; Shihui, Hua (Edelweiss Applied Science and Technology, 2026)
Employee turnover is a significant research topic in management research, and Job Embeddedness has emerged as a key area of focus in turnover research in recent years. This paper employs bibliometric analysis to systematically examine the research trends and hotspots between JE and Turnover and to offer theoretical support and practical insights for future research in this field. This study employs bibliometric analysis and scientific knowledge mapping using CiteSpace to analyze 345 articles retrieved from the Web of Science database. The results show that the number of studies on JE and Turnover has increased significantly since 2010 and has entered a period of rapid growth, especially since 2019. Core contributors include Holtom, Mitchell, and Lee, while the United States and China dominate scholarly output. Research themes have evolved from foundational models to complex mechanisms and emerging application contexts. The study concludes that JE research is entering a stage of diversification and contextual expansion. These findings highlight the need for future research to examine JE across cross-cultural and cross-industry settings, incorporate multi-level analytical approaches, and explore its role in digitalized and flexible work environments, thereby offering more targeted theoretical and practical insights for employee mobility management.